(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The beginning of the Arab Renaissance was cultural when scholars urged for revival and awakening and addressed different fields of knowledge. But what draws the attention is the fact that the majority of pioneers were interested above all by the reform as a way for coming up and advancing to follow up the progress that was taking place in the Western world. This research focuses on Reform, exposing its philosophical principles in the context of the illuminating mission of philosophy on the levels of culture, thought and society. It lists the causes for Reform, and on the factors of revival which inspired the pioneers to expose their visions of present problems and future’s requirements. Also, the research exposes the Reform’s needs and ways as seen by the Renaissance/ Nahda’s intellectuals. In addition to that, it contains a critical review of these forefront enlightened thinkers who, with the available means they had at that time, tried to give a vision for society’s Reform.